EVALUASI PERTAMBAHAN BOBOT BADAN DAN EFISIENSI PENGGUNAAN PAKAN PADA ITIK PEDAGING YANG DIBERI LEVEL AMPAS TAHU YANG BERBEDA - Rasyid, Satri (Journal Galung Tropika, 2012)
This study aimed to evaluate the body weight gain and feed efficiency of the various different levels of tofu on duck meat with intensive farming systems. The usefulness of this research is to find feed formulations using tofu as an alternative feed to increase weight gain and more efficient for feed use, is being used is duck duck king. This research was conducted in the village of Talumae district. Wattang Sidenreng Kab. Sidrap for three months. The study used a base CRD (completely randomized design) with four standard treatment, ie control without giving tofu, tofu waste treatment with the addition of 20%, treatment with the addition of tofu waste 30%, and treatment with the addition of 40% tofu. Each treatment consisted of 4 groups, so there are 16 experimental units, each unit consisting of 6 ducks Raja, a total of 96 observations ducks. The parameters measured were body weight gain (UN) and the efficiency of feed utilization is calculated every week. Results showed Giving tofu tofu in the treatment of 30% can increase body weight broiler ducks better than other treatments, and not significantly different from the control and 20% tofu, but tofu significantly different from 40% at level ?> 0 , 05. Efficiency of feed use in the treatment obtained the lowest score tofu 30% and did not differ very significantly with 40% tofu waste treatment. Being the highest value obtained from the control and did not differ very significantly with 20% tofu waste treatment, but differed significantly with treatment tofu and tofu 30% 40% at level ?> 0.01.